STRATEGIES FOR TEACHING ENGLISH IN NON-NATIVE SPEAKING COUNTRIES: AN INVESTIGATION AT NUKUS STATE PEDAGOGICAL INSTITUTE: STRATEGIES FOR TEACHING ENGLISH IN NON-NATIVE SPEAKING COUNTRIES: AN INVESTIGATION AT NUKUS STATE PEDAGOGICAL INSTITUTE - Pirnazarova, Mehribanum (Журнал иностранных языков и лингвистики, 2025)
In non-native speaking countries, the teaching of English presents unique challenges and opportunities. Conventional language instruction has historically prioritized linguistic competence, often over looking the cultural elements that are indispensable for effective communication. [1; 681] Teachers must navigate cultural, linguistic, and institutional factors that influence language acquisition. Uzbekistan, with its rich linguistic diversity and historical ties to Russian, Uzbek and Karakalpak languages, offers a distinct context for English language education. Nukus State Pedagogical Institute (NSPI), serves as a microcosm of Uzbekistan's educational landscape. The English Language and Literature department at NSPI plays a pivotal role in shaping future educators and advancing English proficiency in the region.